Antimicrobial activity of products based on potassium monopersulfate on bacteria associated with avian infections - Moraes, Miguel Augusto; Oliveira-Silva, Mariana; Goulart, Rafael Silva; Gabarra, Manoel Henrique Cintra; Miranda, Carlos Eduardo Saraiva; Almeida, Paulo Garcia de; Pitondo-Silva, André (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to evaluate the antimicrobial activity of four new potassium monopersulfate-based products on bacterial biofilms associated with avian infections, in order to disinfect drinking fountains in poultry farms. Initially, tests were performed in planktonic bacterial cells, to verify the antimicrobial activity and the minimum inhibitory concentration of the products, named PA, PB, PC, and PD. These products were tested on mature biofilms of the avian pathogens Escherichia coli, Salmonella enterica subsp. enterica serovar Enteritidis, and Listeria monocytogenes, grown on specimens preserved in acrylic blocks, by counting colony-forming units, scanning electron microscopy, and confocal fluorescence microscopy. All products were effective against the evaluated bacterial species. The PA and PB products inhibited the bacterial growth at ≤ 0.13% concentrations, and PC and PD showed the same effect at ≤ 0.25% concentrations. Furthermore, the PA product was able to eliminate mature biofilms of S. enterica subsp. enterica serovar Enteritidis and L. monocytogenes. The evaluated monopersulfate-based products, notably PA, are effective against bacterial biofilms associated with avian infections and show potential as sanitizers and disinfectants for drinking fountains in poultry farms.